2000
DOI: 10.1095/biolreprod63.2.448
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and Vasopressin Expression in the Ovine Testis and Epididymis: Changes with the Onset of Spermatogenesis1

Abstract: Contractions of seminiferous tubules and epididymal duct walls promote spermiation and sperm transfer, and they are thought to be stimulated by the related peptides oxytocin and vasopressin. This study tested the hypothesis that if oxytocin and/or vasopressin play a physiological role in sperm shedding and transport, then local or circulating concentrations of these peptides would increase during puberty. Testes, epididymides, and trunk blood of sheep at stages during the first spermatogenic wave were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 47 publications
2
35
1
1
Order By: Relevance
“…To confirm that OT peptide is present in human epidermis and keratinocytes, the OT content of protein extracts from the tissues and cells was measured by EIA (Table S1). The OT content of human epidermis (160 ± 27 pg/g wet weight) was similar to that of sheep testis (60-130 pg/g by radioimmunoassay) (17). These data suggest that both epidermis and cultured keratinocytes synthesize oxytocin peptide.…”
Section: Resultssupporting
confidence: 58%
“…To confirm that OT peptide is present in human epidermis and keratinocytes, the OT content of protein extracts from the tissues and cells was measured by EIA (Table S1). The OT content of human epidermis (160 ± 27 pg/g wet weight) was similar to that of sheep testis (60-130 pg/g by radioimmunoassay) (17). These data suggest that both epidermis and cultured keratinocytes synthesize oxytocin peptide.…”
Section: Resultssupporting
confidence: 58%
“…HPLC-RIA measurements demonstrated that the Gasserian, L5 ganglia and the celiac ganglia of humans contained significant levels of immunoreactive oxytocin ( Table 3, 4). However, our results…”
Section: Chromatographically Identified Oxytocin In the Human Periphecontrasting
confidence: 58%
“…It plays an important role in neuroendocrine regulation of parturition and lactation (Silverman and Zimmerman, 1983;Sofroniew, 1985). Oxytocin is present not only in the hypothalamo-neurohypophyseal system, but is also located in various areas of the central and peripheral nervous system (Buijs, 1978(Buijs, , 1980 Oxytocin may be involved in the local control of androgen biosynthesis and spermatogenesis in the testis (Assinder et al, 2000). The heart and large vessels like aorta and vena cava are also sites of oxytocin synthesis and the locally produced oxytocin may have important regulatory functions within the heart and the vascular system (Gutkowska et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Many peptides, such as angiotensins (Angs; Fraser et al 2006), kinins (Blaukat 2003), substance P, enkephalins (Sastry et al 1991), endorphin (El-Haggar et al 2006), oxytocin (OXT), vasopressin (AVP; Assinder et al 2000), LHRH (Amory & Bremner 2003), TRH, and fertilization-promoting peptide (FPP; Green et al 1996), as well some peptidases, particularly aminopeptidases (APs) and oligopeptidases have been related to seminal physiology in mammals (Fernández et al 2002, Subirán et al 2008. In this sense, Ang I and II are hydrolyzed by acid AP (APA; EC 3.…”
Section: Introductionmentioning
confidence: 99%